2003
DOI: 10.1104/pp.102.018788
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Cholesterol and Glycoalkaloid Levels in Transgenic Potato Plants by Overexpression of a Type 1 Sterol Methyltransferase cDNA

Abstract: Transgenic potato (Solanum tuberosum cv Désirée) plants overexpressing a soybean (Glycine max) type 1 sterol methyltransferase (GmSMT1) cDNA were generated and used to study sterol biosynthesis in relation to the production of toxic glycoalkaloids. Transgenic plants displayed an increased total sterol level in both leaves and tubers, mainly due to increased levels of the 24-ethyl sterols isofucosterol and sitosterol. The higher total sterol level was due to increases in both free and esterified sterols. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(78 citation statements)
references
References 32 publications
3
73
1
1
Order By: Relevance
“…The presence of the alkyl group at C-24 that originates from this reaction is the structural characteristic differentiating C-24 alkylsterol from cholesterol. Therefore, cholesterol levels in plants are hypothesized to be modulated by SMT; this hypothesis is supported by the lower cholesterol level in transgenic plants that overexpress SMT and the higher cholesterol level in SMT knockout plants (Diener et al, 2000;Schaeffer et al, 2000;Sitbon and Jonsson 2001;Holmberg et al, 2002;Arnqvist et al, 2003). However, the considerable amounts of cholesterol and its derivatives, SGAs, in solanaceous plants have suggested that these plants have a mechanism to produce cholesterol that is distinct from other plants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the alkyl group at C-24 that originates from this reaction is the structural characteristic differentiating C-24 alkylsterol from cholesterol. Therefore, cholesterol levels in plants are hypothesized to be modulated by SMT; this hypothesis is supported by the lower cholesterol level in transgenic plants that overexpress SMT and the higher cholesterol level in SMT knockout plants (Diener et al, 2000;Schaeffer et al, 2000;Sitbon and Jonsson 2001;Holmberg et al, 2002;Arnqvist et al, 2003). However, the considerable amounts of cholesterol and its derivatives, SGAs, in solanaceous plants have suggested that these plants have a mechanism to produce cholesterol that is distinct from other plants.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, cycloartenol is the first D 24(25) -sterol. If cycloartenol is reduced to cycloartanol by SSR2, the biosynthetic pathway would be efficiently redirected toward cholesterol (Figure 1) (Diener et al, 2000;Schaeffer et al, 2000;Sitbon and Jonsson 2001;Holmberg et al, 2002;Arnqvist et al, 2003). We conducted in vitro assays to examine whether SSR2 has cycloartenol reductase activity and to compare the substrate specificities of SSR1 and SSR2 (Figure 4).…”
Section: In Vitro Enzymatic Activity Assays Of Ssrsmentioning
confidence: 99%
“…Consistent with the inability of sterol treatment to complement plants defective in SMT2 (Carland et al, 2010), our attempts to reverse the GAME1i phenotype by application of b-sitosterol and/or stigmasterol were unsuccessful. The effect of GAME1 silencing on sterol metabolism demonstrates once again the tight link between SAs and the sterol pathway (Arnqvist et al, 2003).…”
Section: Phytotoxicity Observed In Game1-silenced Plants and Their Ramentioning
confidence: 92%
“…Alteration of sterol metabolism was also considered as a reason for the morphological changes, since SA and sterol biosynthesis are tightly linked (Arnqvist et al, 2003). Moreover, tomatidine, which accumulates to high levels in GAME1i plants, was reported to mimic the effect of sterol biosynthesis inhibitors (Simons et al, 2006).…”
Section: Game1-silenced Plants Exhibit Altered Sterol Compositionmentioning
confidence: 99%
See 1 more Smart Citation